Revamping the OECD's Five Rural Worlds model for poverty-oriented inter-sectoral analysis, communication and planning - Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
To discuss and plan overall development as well as specific interventions in rural areas of developing countries, it is important to have a comprehensive conceptual model at hand that facilitates communication across sectors involved and which allows generalisations across countries. It should be able to simultaneously bring poverty, economic growth and structural change into focus. This paper presents a conceptual model that can serve these purposes. It builds on the “Five Rural Worlds” (5RWs) model of the Organisation for Economic Co-operation and Development (OECD). It centres on rural populations and classifies them based on a pragmatic, multi-criteria analysis of basic assets and endowments, competitiveness and growth opportunities, and needs, in particular with regards to poverty and food security. The Rural Worlds (RWs) distinguished are 1) large-scale commercial agricultural households and enterprises, 2) traditional landholders and enterprises, 3) subsistence agricultural households and micro-enterprises, 4) landless rural households and micro-enterprises and 5) chronically poor rural households (without family labour force). These distinctions may be crude and blurred, but they are sufficient in many instances to clarify basic assumptions. Being simple enough, they facilitate fundamental and inter-sectoral debates about policy interventions in rural areas. We extend the OECD model to explicitly include interactions between the RWs as well as between these and the outside world. These extensions have been made to highlight the fact that rural areas are increasingly being integrated into national and wider relations, and to allow these relations and their implications to be discussed comprehensively. This modified RW concept has several advantages: It classifies the rural population into a limited number of ubiquitous groupings according to major, common constraints, needs and opportunities. It highlights the importance of land and agricultural technology/productivity as key starting points for pov¬erty, food security and growth opportunities, without excluding the possibility of other livelihood options. It focusses on the rural poor and considers their heterogeneous potential to strive within and/or outside agriculture, in particular distinguishing the landless and chronically poor, who are often left out (or even damaged) by agricultural interventions. It invites thinking about not only the direct effects of policy interventions on different target groups individually, but also about systematically checking indirect second-round effects through the interaction channels. It reminds us of the growing relations between a given rural area and the rest of the world. We advocate the 5RW concept for the inter-sectoral planning of rural development in developing countries, and for multi-sectoral research, in particular in rural sub-Sahara Africa (SSA). We acknowledge that, in addition, a gender and an environmental perspective must be explicitly taken into account, too, which is, however, easily compatible with the model.
Keywords: 330; Armut und Ungleichheit